The Qur'an, Sunnah, and Science: Reactualization of Islamic Values in the Era of the Digital Revolution - Ibnu Abbas; Amiruddin; Luthfiyah; Nurrahmania (CV. Creative Tugu Pena, 2025)
This study examines the integration of the Qur'an and Sunnah as foundational sources of Islamic epistemology in addressing the challenges of Society 5.0. Through a qualitative library research approach, the research analyzes primary and secondary sources, including classical and contemporary Islamic texts, to explore the epistemological framework that harmonizes revelation, reason, and empirical knowledge. The findings reveal that the Qur'an, with its emphasis on 'ilm (knowledge) mentioned over 700 times, and the Sunnah, as the practical interpretation of the Qur'an, collectively form a holistic paradigm for scientific and technological development. The study highlights the concept of Tawhidic Science, which integrates spiritual values with modern advancements, offering ethical guidelines for emerging technologies like AI and big data. Additionally, the research demonstrates how Prophetic traditions provide solutions for contemporary issues such as mental health, environmental sustainability, and social justice. The study concludes that the Qur'an and Sunnah serve as dynamic, living traditions (living tradition) capable of guiding Muslim societies through digital transformation while maintaining moral and spiritual integrity. This integrative approach not only counters the materialistic tendencies of modern science but also fosters a balanced civilization rooted in Islamic values.